PILL BURDEN, SLEEP QUALITY, ANXIETY, DEPRESSION IN PATIENTS WITH DIABETIC AND NON -DIABETIC CHRONIC KIDNEY DISEASE - Basha, Shaik Khaja Shanawaz (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Chronic kidney disease (CKD) has a significant impact upon the quality of life of patients due to multiple factors. One of major stress is due to medication effects which may affect in patients with chronic kidney disease quality of life. In patients with chronic kidney disease, anxiety disorders are often perceived to represent the symptoms of depression and sleep disturbances. Aim and objectives: Therefore the present study evaluated the role of Pill burden, sleep quality, anxiety and depression in patients with diabetic and Non -diabetic chronic kidney disease. Materials and methods: The present study was conducted in 198 pre dialysis CKD patients of 1 to 5 stages with and without Diabetes mellitus. Sleep quality was assessed by using Pittsburgh Sleep Quality Index (PSQI) which is a standard self- reported scale for assessment of sleep quality. Anxiety and depression scores were calculated by using Hospital Anxiety and Depression scale (HADS). Results: With increasing severity of disease burden, CKD patients were found to have more increase in pill burden, reduction in sleep quality, increase in anxiety and depression. This progression was found to be more significant in diabetic CKD patients when compared to non- diabetic CKD patients. Conclusion: The present study findings conclude that patients with advanced stages of CKD experience a high symptom burden that impacts on their daily life. Diabetic CKD patients have been found to be more prone to altered sleep quality, anxiety and depression than non- diabetic CKD patients. Keywords: Chronic kidney disease, Diabetes mellitus, Pill burden, sleeps quality, anxiety and depression.